Portrayal of the Bengkulu City Government in News Coverage of the Relocation of Street Vendors on BETVNews.com - Bakat Seno Pratomo; Evi Lorita; Fanro Fanro; Martha Heriniazwi Dianthi (Universitas Dehasen Bengkulu, 2026)
This study examines how BETVNews.com represents the image of the Bengkulu City Government in its coverage of the street vendor management policy at Pasar Minggu from January to June 2025. The study employs a descriptive qualitative approach within a constructivist paradigm. Eight news articles were selected purposively and analyzed using Robert N. Entman’s framing model, consisting of problem definition, causal interpretation, moral evaluation, and treatment recommendation. The findings reveal two competing frames: public order and legal enforcement as the dominant frame, and traders’ economic survival as the counter-frame. The government is predominantly represented as firm, organized, persuasive, and legitimate in restoring the functions of public space. Nevertheless, a critical image emerges when reports foreground limited relocation capacity, declining income, and conflict during enforcement. The government’s image is therefore ambivalent but asymmetrically positive because official perspectives more frequently structure headlines, leads, causal explanations, and policy solutions. Policy success is also largely measured through visible spatial order, while traders’ post-relocation welfare receives limited evaluation.